#### Answer

$a=-1/6$

#### Work Step by Step

The distributive property allows us to distribute anything multiplied by something inside of the parenthesis to whatever is inside of the parenthesis. Thus, we distribute the -1 to everything inside of the first set of parenthesis, the -1 to everything inside of the second set of parenthesis, and the 2 to everything in the third set of parenthesis, giving us the equation -a+1-3a+2=6+2a-2. We now simplify:
$-4a+3=2a+4 \\\\ 3=6a+4 \\\\ -1=6a \\\\ a=-1/6$